2018
DOI: 10.1097/j.pain.0000000000001414
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptor D2, but not D1, mediates descending dopaminergic pathway–produced analgesic effect in a trigeminal neuropathic pain mouse model

Abstract: Neuropathic pain represents a challenge to clinicians, because it is resistant to commonly prescribed analgesics due to its largely unknown mechanisms. Here, we investigated a descending dopaminergic pathway-mediated modulation of trigeminal neuropathic pain. We performed chronic constriction injury of the infraorbital nerve from the maxillary branch of trigeminal nerve to induce trigeminal neuropathic pain in mice. Our retrograde tracing showed that the descending dopaminergic projection from hypothalamic A11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 56 publications
(88 reference statements)
5
49
2
Order By: Relevance
“…It has been reported that dopamine receptors D1/D5 engage the mechanism of spinal hyperalgesic priming and maintenance of pathological pain plasticity and that D1/D5 agonists induce mechanical hypersensitivity [4]. Our recently published work demonstrates that activation of dopaminergic neurons in the hypothalamic A11 nucleus attenuates peripheral nerve injury-induced neuropathic pain, which is mediated by D2-like dopamine receptors [31]. Taylor and colleagues found that microinjection of selective D2-like dopamine receptor agonist quinpirole in the NAc inhibits formalin-induced persistent nociception in the hind paw [40].…”
Section: Role Of Descending Dopaminergic Pathways In Pain Modulationmentioning
confidence: 76%
See 4 more Smart Citations
“…It has been reported that dopamine receptors D1/D5 engage the mechanism of spinal hyperalgesic priming and maintenance of pathological pain plasticity and that D1/D5 agonists induce mechanical hypersensitivity [4]. Our recently published work demonstrates that activation of dopaminergic neurons in the hypothalamic A11 nucleus attenuates peripheral nerve injury-induced neuropathic pain, which is mediated by D2-like dopamine receptors [31]. Taylor and colleagues found that microinjection of selective D2-like dopamine receptor agonist quinpirole in the NAc inhibits formalin-induced persistent nociception in the hind paw [40].…”
Section: Role Of Descending Dopaminergic Pathways In Pain Modulationmentioning
confidence: 76%
“…However, a recent study reported that although dopamine appears to affect expectations and desires, dopamine changes in the brain do not affect emotional pain in patients with chronic neuropathic pain after placebo intervention [47]. Using von Frey and conditioned place preference tests, we observed that activation of the descending dopaminergic pathway from hypothalamic A11 nucleus to Sp5C inhibits both sensory and emotional components of pain induced by peripheral nerve injury [31].…”
Section: Role Of Descending Dopaminergic Pathways In Pain Modulationmentioning
confidence: 77%
See 3 more Smart Citations